Competitive Drivers of Atrial Fibrillation: The Interplay Between Focal Drivers and Multiwavelet Reentry - Carrick, Richard T.; Benson, Bryce E.; Bates, Oliver R. J.; Spector, Peter S. (Frontiers in Physiology, 2021)
Background: There is debate whether human atrial fibrillation is driven by focal drivers or multiwavelet reentry. We propose that the changing activation sequences surrounding a focal driver can at times self-sustain in the absence of that driver. Further, the relationship between focal drivers and surrounding chaotic activation is bidirectional; focal drivers can generate chaotic activation, which may affect the dynamics of focal drivers. Methods and Results: In a propagation model, we generated tissues that support structural micro-reentry and moving functional reentrant circuits. We qualitatively assessed 1) the tissue’s ability to support self-sustaining fibrillation after elimination of the focal driver, 2) the impact that structural-reentrant substrate has on the duration of fibrillation, the impact that micro-reentrant 3) frequency, 4) excitable gap, and 5) exposure to surrounding fibrillation have on micro-reentry in the setting of chaotic activation, and finally the likelihood fibrillation will end in structural reentry based on 6) the distance between and 7) the relative lengths of an ablated tissue’s inner and outer boundaries. We found 1) focal drivers produced chaotic activation when waves encountered heterogeneous refractoriness; chaotic activation could then repeatedly initiate and terminate micro-reentry. Perpetuation of fibrillation following elimination of micro-reentry was predicted by tissue properties. 2) Duration of fibrillation was increased by the presence of a structural micro-reentrant substrate only when surrounding tissue had a low propensity to support self-sustaining chaotic activation. Likelihood of micro-reentry around the structural reentrant substrate increased as 3) the frequency of structural reentry increased relative to the frequency of fibrillation in the surrounding tissue, 4) the excitable gap of micro-reentry increased and 5) the exposure of the structural circuit to the surrounding tissue decreased. Likelihood of organized tachycardia following termination of fibrillation increased with 6) decreasing distance and 7) disparity of size between focal obstacle and external boundary. Conclusions: Focal drivers such as structural micro-reentry and the chaotic activation they produce are continuously interacting with one another. In order to accurately describe cardiac tissue’s propensity to support fibrillation, the relative characteristics of both stationary and moving drivers must be taken into account.